2020
DOI: 10.1038/s41598-019-57287-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of two novel monoclonal antibodies against overexpressed CD26 and integrin α3 in human pancreatic cancer

Abstract: Monoclonal antibody (mAb) technology is an excellent tool for the discovery of overexpressed cell surface tumour antigens and the development of targeting agents. Here, we report the development of two novel mAbs against CFPAC-1 human pancreatic cancer cells. Using ELISA, flow cytometry, immunoprecipitation, mass spectrometry, Western blot and immunohistochemistry, we found that the target antigens recognised by the two novel mAbs KU44.22B and KU44.13A, are integrin α3 and CD26 respectively, with high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…12 Furthermore, Arias-Pinilla et al have shown that 61% of the 34 tissue samples expressed CD26. 13 These two studies are consistent with our results. Here, we assessed CD26 expression using a larger sample size and analyzed in detail its correlation with various clinicopathological features.…”
Section: Discussionsupporting
confidence: 93%
“…12 Furthermore, Arias-Pinilla et al have shown that 61% of the 34 tissue samples expressed CD26. 13 These two studies are consistent with our results. Here, we assessed CD26 expression using a larger sample size and analyzed in detail its correlation with various clinicopathological features.…”
Section: Discussionsupporting
confidence: 93%
“…The results from cell proliferation assays in human pancreatic cancer cell lines, cell line-based xenografts and patient-derived tumour xenografts have demonstrated antitu-mour activity either as single agents or in combination with cytotoxic drugs. The results of in vitro studies have supported the therapeutic potential of mAbs targeting integrin α3 [26], MUC4 [27], MUC1 [28], and MUC13 [29] when used alone or in combination with cytotoxic drugs. Furthermore, mAbs targeting EGFR, TROP2 and α6β4 have been used for radioimmunotherapy and have shown effective localisation of primary tumours and metastatic sites in mouse models [30][31][32].…”
Section: Preclinical Studiesmentioning
confidence: 84%
“…Indeed, using monoclonal antibody technology and human pancreatic cancer cell lines established from primary tumours and metastatic sites, both as the source of tumour immunogen and in the antibody screening, we have reported recently the development of three novel antibodies. We found that the antigens recognised by these three novel mAbs were CD109, integrin α3 and CD26, with high levels of expression in several human pancreatic cancer cells and Pancreatic Cancer Tissue microarray [26,66]. Indeed, antibody-based screening will help not only in the discovery of additional therapeutic cell surface antigens with high levels of expression at different stages of pancreatic cancer (i.e., therapeutic targets) but also in the development of antibody-based agents for therapy.…”
Section: Challenges and Future Opportunities With Antibody Therapeutics In Pancreatic Cancermentioning
confidence: 98%